Quality Metrics and Reliability Analysis of Laser Communication System - Raj, A. Arockia Bazil; Padmavathi, S. (Defence Science Journal, 2016)
Beam wandering is the main cause for major power loss in laser communication. To analyse this prerequisite at our environment, a 155 Mbps data transmission experimental setup is built with necessary optoelectronic components for the link range of 0.5 km at an altitude of 15.25 m. A neuro-controller is developed inside the FPGA and used to stabilise the received beam at the centre of detector plane. The Q-factor and bit error rate variation profiles are calculated using the signal statistics obtained from the eye-diagram. The performance improvements on the laser communication system due to the incorporation of beam wandering mitigation control are investigated and discussed in terms of various communication quality assessment key parameters.